Unlocking the potential of glyphosate-resistant bacterial strains in biodegradation and maize growth - Mohy-Ud-Din, Waqas; Chen, Feng; Bashir, Safdar; Akhtar, Muhammad Javed; Asghar, Hafiz Naeem; Farooqi, Zia Ur Rahman; Zulfiqar, Usman; Haider, Fasih Ullah; Afzal, Aneeqa; Alqahtani, Mashael Daghash (Frontiers in Microbiology, 2023)
Glyphosate [N-(phosphonomethyl)-glycine] is a nonselective herbicide with a broad spectrum that is commonly used to control perennial vegetation in agricultural fields. The widespread utilization of glyphosate in agriculture leads to soil, water, and food crop contamination, resulting in human and environmental health consequences. Therefore, it is imperative to devise techniques for enhancing the degradation of glyphosate in soil. Rhizobacteria plays a crucial role in degrading organic contaminants. Limited work has been done on exploring the capabilities of indigenously existing glyphosate-degrading rhizobacteria in Pakistani soils. This research attempts to discover native bacteria having glyphosate degrading ability for a sustainable solution to glyphosate contamination.Therefore, this study explored the potential of 11 native strains isolated from the soil with repeated glyphosate application history and showed resistance against glyphosate at higher concentrations (200 mg kg -1 ). Five out of eleven strains outperformed in glyphosate degradation and plant growth promotion. High-pressure liquid chromatography showed that, on average, these five strains degraded 98% glyphosate. In addition, these strains promote maize seed germination index and shoot and root fresh biomass up to 73% and 91%, respectively. Furthermore, inoculation gave an average increase of acid phosphatase (57.97%), alkaline phosphatase (1.76 folds), and dehydrogenase activity (1.75 folds) in glyphosate-contaminated soil. The findings indicated the importance of using indigenous rhizobacteria to degrade glyphosate. So, by maintaining soil health, indigenous soil biodiversity can work effectively for the bioremediation of contaminated soils and sustainable crop production in a world facing food security.